2013
DOI: 10.1186/1471-2474-14-323
|View full text |Cite
|
Sign up to set email alerts
|

Birth prevalence for congenital limb defects in the northern Netherlands: a 30-year population-based study

Abstract: BackgroundReported birth prevalences of congenital limb defects (CLD) vary between countries: from 13/10,000 in Finland for the period 1964–1977 to 30.4/10,000 births in Scotland from 1964–1968. Epidemiological studies permit the timely detection of trends in CLD and of associations with other birth defects. The aim of this study is to describe the birth prevalence of CLD in the northern Netherlands.MethodsIn a population-based, epidemiological study we investigated the birth prevalences of CLD for 1981–2010. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 28 publications
5
74
0
8
Order By: Relevance
“…Polydactyly and syndactyly were the second and third most common CLDs in our study, which is consistent with other studies in both western and Asian countries (Aro et al ; Padilla et al ; Zhang et al ; Li et al ; Vasluian et al ) including the studies in Thailand noted earlier (Siripoonya and Tejavej ; Dissaneevate et al ). Polydactyly occurred in the upper extremities three times as often as in the lower extremities, while syndactyly affected the lower extremities at twice the rate as in the upper extremities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Polydactyly and syndactyly were the second and third most common CLDs in our study, which is consistent with other studies in both western and Asian countries (Aro et al ; Padilla et al ; Zhang et al ; Li et al ; Vasluian et al ) including the studies in Thailand noted earlier (Siripoonya and Tejavej ; Dissaneevate et al ). Polydactyly occurred in the upper extremities three times as often as in the lower extremities, while syndactyly affected the lower extremities at twice the rate as in the upper extremities.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence rate of congenital limb reductions in our study was 0.18 per 1000 births which is within the variance of prevalence rates reported in other Asian countries of 0.15–0.42 per 1000 births (Siripoonya and Tejavej ; Dissaneevate et al ; Makhoul et al ; Padilla et al ; Zhang et al ; Li et al ). The reason for lower prevalence rates of limb reductions in Asian countries than the prevalence rates in western countries of 0.50–0.79 per 1000 births (Aro et al ; Froster‐Iskenius and Baird ; Evans et al ; McQuirk et al ; Rankin et al ; Dolk et al ; Parker et al ; Gold et al ; Vasluian et al ; Calzolari et al ) is currently unknown, but could be related to different genetic and environmental factors. In our study, limb reduction involved an upper limb or limbs about twice as often as lower limb or limbs, a finding which is similar to studies from both Caucasian and Asian countries (Aro et al ; Froster‐Iskenius and Baird ; Evans et al ; McQuirk et al ; Parker et al ; Gold et al ; Zhang et al ; Li et al ; Vasluian et al ; Calzolari et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 A recent European study reported a prevalence of congenital limb defects as 21.1/10,000. 11 Other studies have reported different incidence of congenital malformations, Perveen and Tyyab reported a prevalence of 11.4/1000 births. In present study, the overall prevalence found was 6.7 per thousand live births.…”
Section: Discussionmentioning
confidence: 99%
“…18 To date, there is no commonly accepted measure of self-reported hand function among these children. Although some aspects of hand function can easily be obtained by functional assessment, such as grip or pinch strength, these measures do not always reflect disability.…”
mentioning
confidence: 99%